2007
DOI: 10.1158/1535-7163.mct-06-0448
|View full text |Cite
|
Sign up to set email alerts
|

Dual mitogen-activated protein kinase and epidermal growth factor receptor inhibition in biliary and pancreatic cancer

Abstract: This study aimed to develop rational combinations of targeted agents against biliary and pancreatic cancers. To this end, we compared the global gene expression profile of biliary cancer cell lines with different degrees of sensibility to the epidermal growth factor receptor tyrosine kinase inhibitors gefitinib and erlotinib using the Affymetrix U133A microarray platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Moreover, the results of this study showed that rare and potentially "druggable" oncogenic mutations may exist in many common tumor types regarded as WT against well-known oncogenes (20). Thus, there is a clear need for more rational therapeutic strategies of genetically complex tumor cells, and several studies have already provided initial rational combination therapies (22)(23)(24). In this study, we characterize AZD6244 (ARRY-142886), a novel MAP/ERK kinase (MEK) inhibitor that exerts antiproliferative effects on human gastric cancer cell lines that are resistant to gefitinib.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, the results of this study showed that rare and potentially "druggable" oncogenic mutations may exist in many common tumor types regarded as WT against well-known oncogenes (20). Thus, there is a clear need for more rational therapeutic strategies of genetically complex tumor cells, and several studies have already provided initial rational combination therapies (22)(23)(24). In this study, we characterize AZD6244 (ARRY-142886), a novel MAP/ERK kinase (MEK) inhibitor that exerts antiproliferative effects on human gastric cancer cell lines that are resistant to gefitinib.…”
Section: Introductionmentioning
confidence: 85%
“…EGFR (exons [18][19][20][21][22][23][24], KRAS (exons 1-3), and BRAF (exon 15) were then sequenced using the previously described primers and methods (10,25,26). All sequencing reactions were conducted in the forward and reverse directions.…”
Section: Methodsmentioning
confidence: 99%
“…S1). 5 However, a dose of 1 Amol/L was selected for in vitro experiments to reduce direct cytotoxic effects. In Western blot analysis, stimulation of endothelial cells with VEGF-A led to an activation of Erk and SAPK signaling intermediates and NVP-AAL881 markedly reduced phosphorylation of these intermediates (Fig.…”
Section: Effects Of Raf/vegfr2 Inhibition On Endothelial Cells and Pementioning
confidence: 99%
“…In pancreatic cancer, RasRaf-MAPK signaling is required for mediating growth factor-induced (such as epidermal growth factor) oncogenic effects and activation of this pathway is associated with tumor progression (proliferation) and invasiveness (cell migration; refs. 4,5). Moreover, it was shown that dual MAPK/epidermal growth factor receptor inhibition significantly decreases growth of KRAS-mutated pancreatic cancer tumors in preclinical models, whereas solely blocking epidermal growth factor receptor (erlotinib) has no growth-inhibitory effect, suggesting that targeting the RasRaf-MAPK pathway is superior to anti-epidermal growth factor receptor therapy in KRAS-mutated pancreatic cancer (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation